2012
DOI: 10.1186/1754-6834-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the simultaneous production of laccase and lignin peroxidase from Streptomyces cinnamomensis by medium formulation

Abstract: BackgroundUse of crude ligninase of bacterial origin is one of the most promising ways to improve the practical biodegradation of lignocellulosic biomass. However, lignin is composed of diverse monolignols with different abundance levels in different plant biomass and requires different proportions of ligninase to realize efficient degradation. To improve activity and reduce cost, the simultaneous submerged fermentation of laccase and lignin peroxidase (LiP) from a new bacterial strain, Streptomyces cinnamomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…The media supplement with corn cob and sugarcane pith characterized by tiny induction effect, where laccase level slightly climbed up by 7.9 and 6.6% more than control trial. However, the rice straw and rice bran had not significant effect on laccase production; about 1.9 and 0.9% more increase than the control trial with observations reported by other investigators [9,17,25] who found that rice straw, wheat bran, peanut shell, banana peel, and black grapes were identified as promising substrates for laccase production, while the other substrates like corn cops, rice straw, and sugarcane bagasse caused low laccase production. However, the observation documented by other investigators [26,27] are compatible with the results of this study in term of apple and wheat bran caused decline in laccase production.…”
Section: Utilization Of Sugarcane Bagasse and Black Liquor For Media supporting
confidence: 55%
“…The media supplement with corn cob and sugarcane pith characterized by tiny induction effect, where laccase level slightly climbed up by 7.9 and 6.6% more than control trial. However, the rice straw and rice bran had not significant effect on laccase production; about 1.9 and 0.9% more increase than the control trial with observations reported by other investigators [9,17,25] who found that rice straw, wheat bran, peanut shell, banana peel, and black grapes were identified as promising substrates for laccase production, while the other substrates like corn cops, rice straw, and sugarcane bagasse caused low laccase production. However, the observation documented by other investigators [26,27] are compatible with the results of this study in term of apple and wheat bran caused decline in laccase production.…”
Section: Utilization Of Sugarcane Bagasse and Black Liquor For Media supporting
confidence: 55%
“…isolated from termite Amitermes hastatus have indicated production of laccases, lignin peroxidases, or manganese peroxidases enzymes by them [ 118 ]. Laccase and lignin peroxidase activities have also been observed in Streptomyces cinnamomeus [ 119 ]. Laccase enzyme studies were carried out including their structural elucidation in Streptomyces lavendulae , Streptomyces psammoticus , Streptomyces ipomoeae , and Streptomyces sviceus [ 61 ].…”
Section: Diversity Of Lignocellulolytic Actinomycetesmentioning
confidence: 99%
“…), and obligate anaerobic species (such as Clostridium sp.) have been identified as the dominant species (Brück et al, 2010;Jing, 2010;Jing and Wang, 2012). Although the difference in microbial community composition can be observed in electrophoretic profiles obtained by DGGE (Kent and Triplett, 2002), no definite correlation was found between the diversity of bacterial communities (Supplementary Data 3-a-e) and the comprehensive G average (Supplementary Data 4-a-d).…”
Section: Detection Of Sedimentary Bacteriamentioning
confidence: 89%